2022
DOI: 10.1021/acsanm.2c02746
|View full text |Cite
|
Sign up to set email alerts
|

Single-Atom Pd Catalysts Supported on Covalent Triazine Frameworks for Hydrogen Production from Formic Acid

Abstract: According to our knowledge, single-atom Pd catalysts supported on covalent triazine frameworks (CTF) have not been studied in the production of hydrogen from formic acid. Therefore, we synthesized 1 wt % Pd single-atom catalysts based on CTF-1, pyCTF, and bipyCTF supports and tested them in the gas-phase decomposition of formic acid. The results were compared with those obtained for a Pd catalyst supported on mesoporous graphitic-type carbon (Pd/C) with nanoparticles (∼2.3 nm). The catalysts were characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 58 publications
1
24
0
Order By: Relevance
“…Despite washing the samples in HCl, water, and tetrahydrofuran, X-ray photoelectron spectroscopy (XPS) analysis showed that some amounts of Zn and Cl were left in the hatnCTF sample (Table S1) but not in the acacCTF sample. This is in accordance with literature data for other CTF samples. , …”
Section: Methodssupporting
confidence: 94%
See 3 more Smart Citations
“…Despite washing the samples in HCl, water, and tetrahydrofuran, X-ray photoelectron spectroscopy (XPS) analysis showed that some amounts of Zn and Cl were left in the hatnCTF sample (Table S1) but not in the acacCTF sample. This is in accordance with literature data for other CTF samples. , …”
Section: Methodssupporting
confidence: 94%
“…Electron microscopy studies were performed using a double-corrected ThemisZ (Thermo Fisher Scientific) device in high-angle annular dark-field/scanning transmission electron microscopy (HAADF/STEM) and high-resolution transmission electron microscopy (HRTEM) modes with an acceleration voltage of 200 kV …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…78 By implanting metal single atoms into CTFs, the process of intermediate evolution and conversion happens more smoothly and the energy barrier will decrease because of the electron transfer and orbital overlaps between the d electrons of metals and the molecular orbitals of substrates. [79][80][81][82] As a representative work, Liang's group applied triazine COF supported Pd single atoms (Pd 1 /trzn-COF) in CO oxidation and illustrated the detailed roles of Pd single atoms and the trzn-COF as well as the corporative catalysis based on their chemical interactions. 14 Engineering active metals into CTFs for photocatalysis Photocatalysis, as a critical subclass of conversion and storage of solar energy, has gained huge popularity in the scientic fraternity.…”
Section: Engineering Active Metals Into Ctfs For Thermocatalysismentioning
confidence: 99%